Analysis Of The Speech Act Of Compliment In Multicultural Society: A Case Study - Endarti, Evi (Dinasti International Journal of Education Management And Social Science, 2024)
This qualitative study examines how people in a multicultural society express their specific intentions through compliments. As a case study, data were taken from the English transcriptions of characters’ dialogues in the Netflix series Emily in Paris Seasons 1 and 2. This Netflix series  is the proper example of a society whose members come from diverse cultural backgrounds, both native and non-native English speakers. According to the findings, skill/ performance is the most frequent topic, it is assumed that the majority of characters appreciate individuals’ ability or expertise when they give compliments. In addition, the functions of using compliments vary depending on the speakers’ intention. The results show that some compliments have implicit meanings. Characters tend to use the speech act of compliments to convey their negative emotions (e.g., expressing disappointment, criticism) to preserve others' face or self-image regarding polite behaviour in social relationships. Therefore, this study is expected to provide a broader perspective on the use of compliments for certain purposes. Since compliment is considered as one of positive politeness strategies, it is useful to bridge the gap and  navigate social communication among people in multicultural soceity with different cultural backgrounds, values, and norms.